Color, Material and Finish (CMF) design innovation and cultural integration: exploring smart digital gadgets differentiated design - Chen, Guanglin; bin Dolah, Mohd Shahrizal; bin Ramli, Saiful Hasley (Human Resources Management Academic Research Society (HRMARS), 2024)
This study explores the cultural and emotional factors in the design of Smart Digital Gadgets (SDGs), particularly focusing on the application of CMF (Color, Material, and Finish) design. Despite the rapid technological advancements in SDGs in the digital era, there is a prevalent issue of design homogenization, leading to a lack of emotional and cultural connection with users. Through a literature review, this study identifies the current problems in SDGs design and proposes a new framework that integrates cultural design and CMF design to enhance user experience and product differentiation. Using Ibrahim's unique “Literature Review Synthesis Process” method, 26 relevant articles were selected and analyzed from Scopus and Google Scholar, resulting in the identification of three main themes: Smart Digital Gadgets Design, CMF Design and Research Methods, and Cultural Feature Design and Application. The findings suggest that integrating cultural dimensions into CMF design can enhance the visual design theoretical framework of SDGs and promote cultural inheritance. This study provides guidance for future SDGs design practices and academic research, emphasizing the importance of cultural and emotional design in meeting consumer needs. Future research will continue to explore the integration of cultural dimensions and emotional design methods in CMF design.